Strategi Menuju Kabupaten Lengkap dengan terus mengakselerasi program Pendaftaran Tanah Sistematis Lengkap (PTSL) di Kantor Pertanahan Kabupaten Pati - Hidayati, Triana; Silviana, Ana (LPPM Universitas Ekasakti Padang, 2024)
In an effort to realize the Modern Land Office as an electronic-based land and space information service center, the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN) launched a Complete City/Regency declaration program. The Complete Systematic Land Registration Program (PTSL) is an asset legalization program with a systematic land registration scheme, which means registration starts from village to village, district/city to other districts/cities, until it is completely registered throughout Indonesia. A strategy to improve data quality is needed to accelerate PTSL so that it can move towards a fully registered and mapped Indonesia as well as preparation for facing the main obstacles in realizing a complete district in Pati Regency. This research uses an empirical juridical research method, namely by knowing the strategy for accelerating the PTSL program in accordance with the legal regulations in force at the Pati Regency Land Office. The data sources used in this research are primary data sources and secondary data. Data collection was carried out by means of observation and interviews. This research data analysis is connected to problems which are then researched and described in narrative form. From this research, it can be obtained how the strategy for improving data quality in realizing a Complete City/Regency can be seen from the spatial aspect and the obstacles faced in realizing a Complete District at the Pati Regency Land Office are known.